Ads in gaming apps: experiential value of gamers. Issue 1 (5th October 2021) - Valaei, Naser; Bressolles, Gregory; Khan, Hina; Low, Yee Min
Abstract : Purpose: Even though there is a noticeable market value in the mobile gaming apps industry, there has been limited research examining experiential value of gamers with respect to in-game ads in gaming apps. This study fills the void in the literature by examining factors associated with "experiential value of gamers through ads in gaming apps" as well as investigating its antecedents (cognitive and affective involvement) and consequences (positive word of mouth and intention to continue playing the mobile game). Design/methodology/approach: A total of 600 valid responses from gamers was used to test the model fit, measurement and structural models, conditional probabilistic queries, and nonlinearity. Findings: This study found that experiential value of gamers through ads in gaming apps is a second-order factor of four constructs: escapism, enjoyment, social affiliation and entertainment. Most of the structural paths between cognitive/affective involvement and dimensions of experiential value are supported. Surprisingly, only social affiliation and entertainment values predict positive word of mouth and intention to continue playing the mobile game, in a nonlinear way. Originality/value: This study is the first to introduce "experiential value of gamers through ads in gaming apps". The findings have important implications for companies to develop brand and communication strategies by leveraging specific advertisement formats and present their ads to the right audience in the right gaming apps and at the right time.